America is Dead. Long Live America! Political Affect in Days Gone - Soraya Murray (European Journal of American Studies)
This essay models a method for understanding political affect in video games by analyzing the American action-adventure survival horror game Days Gone (SIE Bend Studio, 2019). Through an examination of its rendering of the Pacific Northwest landscape as ideology, much is revealed about a deeply troubled and oppositional worldview. While this research addresses matters of representation—particularly notions of fraught masculinity and a struggle for recognition—its focus is on how the game functions as a window onto a fantasy of American self-reliance and populism that strongly resonates with a Trump-era nationalist turn in the U.S. The essay also gestures toward a methodology of experiential close-reading, one focused on working-through and sitting with a difficult aesthetic object that may at first seem entirely generic. In this essay, the author reaches through the offending, formulaic image to grasp the political affect that emanates from a sustained aesthetic experience of playing Days Gone.